2010
DOI: 10.3164/jcbn.10-53
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mulberry Leaf Extract Rich in 1-Deoxynojirimycin on Blood Lipid Profiles in Humans

Abstract: Mulberry leaves are rich in 1-deoxynojirimycin (DNJ), an inhibitor of α-glucosidase. We previously showed that DNJ-rich mulberry leaf extract suppressed elevation of postprandial blood glucose in humans. The objective of this study was to evaluate the effects of DNJ-rich mulberry leaf extract on plasma lipid profiles in humans. An open-label, single-group study was conducted in 10 subjects with initial serum triglyceride (TG) level ≥200 mg/dl. Subjects ingested capsules containing DNJ-rich mulberry leaf extrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(62 citation statements)
references
References 15 publications
1
59
0
2
Order By: Relevance
“…Several studies have already investigated various alkaloids, flavonoids and phytochemicals in white mulberry leaves to improve dyslipidemia, especially hypercholesterolemia (29) and inhibit oxidation of LDL-cholesterol (30). The hypolipidemic effect of mulberry leaf extract in healthy non-diabetic human subjects was investigated and showed no significant difference in serum lipid profile, indicating the hypolipiemic effect of mulberry leaf tea may not be similar between normal and diabetic persons (31).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already investigated various alkaloids, flavonoids and phytochemicals in white mulberry leaves to improve dyslipidemia, especially hypercholesterolemia (29) and inhibit oxidation of LDL-cholesterol (30). The hypolipidemic effect of mulberry leaf extract in healthy non-diabetic human subjects was investigated and showed no significant difference in serum lipid profile, indicating the hypolipiemic effect of mulberry leaf tea may not be similar between normal and diabetic persons (31).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, white mulberry fruits widely distributed in Egyptian agriculture are used to protect from liver and kidney damage, strengthen the joints, improve eyesight, and have anti-aging and radio protective effects [15,18,19]. In addition, recent studies have reported that 1-deoxynojirimycin in white mulberry has anti-diabetic effects and it reduces postprandial blood glucose levels through inhibition of α-glucosidase and decrease of serum triglyceride levels [20,21]. The black mulberry fruit (M. nigra) is reported to possess antioxidant effect due to presence of phenolic compounds and anthocyanins [22].…”
Section: Introductionmentioning
confidence: 99%
“…8,10) No adverse events occurred during the human studies. 8,10,11) Therefore, this DNJenriched product may represent a therapy for oral treatment of non-insulin-dependent diabetes mellitus (type 2 diabetes). This possibility is now under investigation by our group in clinical studies in order to obtain ''Food for Specified Health Use (FOSHU)'' status in Japan.…”
mentioning
confidence: 99%